Fluxnet Product from Hyltemossa - Michal Heliasz; Natascha Kljun; Tobias Biermann; Jutta Holst; Thomas Holst; Peter Kornacher; Maj-Lena Linderson; Meelis Molder; Janne Rinne (Integrated Carbon Observation System, 2025)
Subset of half-hourly Fluxes and Meteo measurements processed with the international standard FLUXNET procedure (ONEFlux suite) for fast plotting purposes. Full data available in the Archive product.
Heliasz, M., Kljun, N., Biermann, T., Holst, J., Holst, T., Kornacher, P., Linderson, M., Molder, M., Rinne, J. (2025). Fluxnet Product from Hyltemossa, 2017-12-31–2024-12-31, FLUXNET, https://hdl.handle.net/11676/Ct67_mNnBo8HATmj0vY4idjm
Keywords: Ecosystem Thematic Centre; carbon flux; pre-ICOS; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; incoming shortwave radiation; incoming shortwave radiation; latent heat flux; latent heat flux; sensible heat flux; sensible heat flux; net ecosystem exchange; net ecosystem exchange; vapour pressure deficit; vapour pressure deficit; ecosystem respiration; ecosystem respiration; gross primary CO2 production; gross primary CO2 production; quality flag (int); quality flag (int); incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; quality flag; quality flag; precipitation (total); precipitation (total); atmospheric pressure; atmospheric pressure; wind speed; wind speed; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap